The Effect of the Methods of Basic Soil Treatment on its Agrophysical Parameters - Iljasovich Mamsirov, Nurbiy; Alekseevich Chumachenko, Yuri; Cherimovich Udzhuhu, Asker; Khalidovich Khatkov, Kazbek (International Journal of Engineering and Technology, 2018)
The article presents the results of years of research conducted in order to establish the optimal parameters of agrophysical soil properties with different ways of its treatment in the agrotechnologies of row crop production. The studies were conducted on the following soil treatment systems: plowing the soil to a depth of 25-27 cm (at a stretch (control); chisel soil treatment to a depth of 38-40 cm (at a stretch); surface treatment of the soil to a depth of 10-12 cm (at a stretch); and combined soil treatment system. The study demonstrated the typical relationship between the structure and density of the compact chernozem, different for the seed and the underlying layers. The parameters of the agrophysical indices of the compact chernozem, which are actually attainable over the arable layer and favorable for tilled field crops, have been theoretically justified and experimentally confirmed.It has been found that for compact chernozem with high and persistent water stability (more than 68%) of the soil structure, unfavorable agrophysical indices are characteristic, sharply differentiated according to its layers: 1) the amount of blocky soil suite (structural aggregates of more than 10.0 mm) can reach 55% in the upper and 90% in the underlying layers of the arable layer; 2) the density of the arable layer of the soil is reduced to 0.94 g/cm3, while in the 15-25 cm and 30-40 cm layers it increases to 1.34 g/cm3.A correlation has been found between the density and share of the blocky fraction, negative in the 0-10 cm soil layer, and positive in the deeper layers. With an increase in the share of the blocky fraction, the upper layer of the soil acquires a loose structure (total porosity of above 60%), and the lower layers are compacted with a decrease in porosity to 50%.
Keywords: soil; compact leached chernozem; soil structure; soil density; granulometric composition; porosity; row crops; corn; sunflower; soil treatment; yield.